If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2+3x+7=6x+5+x
We move all terms to the left:
-2+3x+7-(6x+5+x)=0
We add all the numbers together, and all the variables
3x-(7x+5)-2+7=0
We add all the numbers together, and all the variables
3x-(7x+5)+5=0
We get rid of parentheses
3x-7x-5+5=0
We add all the numbers together, and all the variables
-4x=0
x=0/-4
x=0
| 2(2x+2+)=5x-8 | | 300x-83=x | | 3y+1=6y−3+4y | | 3,200/160=x | | 11x-24=2(5x+9) | | 18x=4x+5 | | 11x-24=2(5x+9 | | .66x=1 | | y=4-4+3 | | y=4-0+3 | | 5a+20=-6a | | y=24-3(4) | | 7x-24=3x+6 | | X×12+50=10x | | 17-y=291 | | 4(x-0.03)^2=(0.01+x)^2 | | 140=202-y | | 2x-8-4x=16 | | 202=-u+54 | | 4(x-0.03)^2=(0.01 | | 8x-2(5x-4)=-12 | | 9x-(2x+5)=4x-7 | | 0.6x+3=2x+.2 | | 4x+2=4x+17 | | 4x+2=4+17 | | 8(c+1)+4=3(2c-8)-16 | | 3(g1)+7=3g+4 | | 7x-3/x-1=2/3 | | 53-6=13-10x | | 3(x-2)=13=(2x+5) | | m=14.556851+255-m=124 | | 5x+5=8x+11 |